Human Papillomavirus Vaccine Recommendations and Agreement with Mandated Human Papillomavirus Vaccination for 11-to-12-Year-Old Girls: a Statewide Survey of Texas Physicians - Jessica A. Kahn; H. Paul Cooper; Susan T. Vadaparampil; Barbara C. Pence; Armin D. Weinberg; Salvatore J. LoCoco; Susan L. Rosenthal (2009)
Abstract Background: The purpose of this study was to examine Texas physicians' recommendations for the quadrivalent human papillomavirus (HPV) vaccine in 11-to-12-year-old girls, intention to recommend HPV vaccines to 11-to-12-year-old boys, and attitudes about mandated HPV vaccination for 11-to-12-year-old girls. Materials and Methods: We conducted a cross-sectional, web-based survey of Texas physicians who provide direct patient care in family medicine, pediatrics, obstetrics/gynecology, and internal medicine in September 2008. The three outcome variables were: HPV vaccine recommendations to 11-to-12-year-old girls, likelihood of recommending the vaccine to 11-to-12-year-old boys, and agreement with mandated vaccination of 11-to-12-year-old girls. Univariate and logistic regression analyses were used to determine practice-related and attitudinal factors associated with each outcome. Results: Of the 1,122 respondents, 48.5% stated they always recommended HPV vaccines to girls, 68.4% were likely to recommend the vaccine to boys, and 41.7% agreed with mandated vaccination. In multivariate logistic regression models, variables independently associated with recommendation to 11-to-12-year-old girls included: percentage of patients with Medicaid [odds ratio (OR), 1.02; 95% confidence interval (95% CI), 1.01-1.03], academic versus nonacademic practice (OR, 2.11; 95% CI, 1.05-4.23), office procedures to maximize vaccination (OR, 1.25; 95% CI, 1.01-1.56), HPV knowledge (OR, 1.25; 95% CI, 1.04-1.49), valuing HPV vaccine information from both professional organizations (OR, 1.90; 95% CI, 1.15-3.16) and professional conferences (OR, 1.68; 95% CI, 1.10-2.57), belief in mandated HPV vaccination (OR, 5.38; 95% CI, 3.28-8.83), and barriers to vaccination (OR, 1.08; 95% CI, 1.00-1.16). Discussion: Half of the physicians in this study did not follow current recommendations for universal HPV vaccination of 11-to-12-year-old girls. Factors linked to vaccine recommendations may be targeted in educational or policy interventions. (Cancer Epidemiol Biomarkers Prev 2009;18(8):2325–32)